The Influence of Receivables, Financing, and Non-Profit Sharing on the Profitability of Sharia Commercial Banks in Indonesia - Farida, Ida; Putri, Tutik Sukmalasari; Susianti, Nurul; Fitriani, Fitriani (Prodi Ekonomi Syariah Pascasarjana IAIN Kudus, 2023)
This study aims to assess the impact of receivables, financing, and non-profit sharing on the profitability of Sharia Commercial Banks in Indonesia during the 2020-2022 period. The study includes Chow tests and classic assumption tests by employing a quantitative research approach with a multiple linear regression data analysis model. Secondary data is gathered from quarterly financial statements of four Sharia Commercial Banks that meet the necessary criteria and are registered with the Indonesia Financial Services Authority (OJK). The findings indicate that Qardh receivables and Musharakah financing positively and significantly influence profitability. However, Murabahah receivables, Musharakah financing, and non-profit sharing do not significantly impact the profitability of Islamic commercial banks during the specified period. In conclusion, variables such as Qardh, Murabahah, Mudharabah financing, Musharakah, and non-profit sharing are significant factors that affect profitability. This study suggests a need for increased attention to factors influencing financing and emphasizes that a comprehensive understanding of non-profit sharing can enhance the distribution of financing funds, consequently improving the profitability and performance of Islamic banks.